Frequency characteristic of the acoustic emission signal in concrete under compressive loading - POGAN, K. (Archives of Acoustics, 1998)
Acoustic Emission measurements are very useful in the investigation of changes taking place in a composite during compressive tests. Among the AE intensity measurements (i.e. counts rate, root mean square, etc.) also the frequency analysis of the AE signal seems to be the useful method. In this paper the analysis of the AE signal characteristic for six different concrete compositions, also for those with silica fumes, is presented. Acoustic Emission signals were measured during quasi-axial compressive tests. The main aim of presented investigations was to demonstrate the spectral patterns of the AE waveforms generated by different concrete structures under compressive loading.